2013
DOI: 10.1007/s00198-013-2463-x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk following bariatric surgery: a population-based study

Abstract: Summary The effects of bariatric surgery on skeletal health are poorly understood. We found that bariatric surgery patients are more prone to fracture when compared to the general population. While further studies of fracture risk in this population are needed, bone health should be discussed in bariatric surgery clinics. Introduction Bariatric surgery is an increasingly common treatment for medically complicated obesity. Adverse skeletal changes after bariatric surgery have been reported, but their clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
174
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(193 citation statements)
references
References 47 publications
4
174
0
10
Order By: Relevance
“…In keeping with these findings, a population-based, historical cohort study of the medical records of 258 patients that had bariatric surgery between 1985 and 2004 found that these patients, over 94% of which had RYGB, carried a higher fracture risk than that of the general population, with an odds ratio of 2.3 (1.8-2.8) [67]. This risk was higher for fractures not only at the traditional osteoporotic sites of the hip, wrist, spine and upper arm, but also at nonosteoporotic sites such as the foot, leg or hand [67]. These two studies [66,67] are in contrast to a population-based, retrospective cohort study on 2079 surgical patients, which found no evidence of association between bariatric surgery and fracture [68].…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 82%
See 3 more Smart Citations
“…In keeping with these findings, a population-based, historical cohort study of the medical records of 258 patients that had bariatric surgery between 1985 and 2004 found that these patients, over 94% of which had RYGB, carried a higher fracture risk than that of the general population, with an odds ratio of 2.3 (1.8-2.8) [67]. This risk was higher for fractures not only at the traditional osteoporotic sites of the hip, wrist, spine and upper arm, but also at nonosteoporotic sites such as the foot, leg or hand [67]. These two studies [66,67] are in contrast to a population-based, retrospective cohort study on 2079 surgical patients, which found no evidence of association between bariatric surgery and fracture [68].…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 82%
“…In subgroup analysis, this association between bariatric surgery and increased fracture risk was found to be stronger with RYGB surgery than with sleeve gastrectomy or other surgery types [66]. In keeping with these findings, a population-based, historical cohort study of the medical records of 258 patients that had bariatric surgery between 1985 and 2004 found that these patients, over 94% of which had RYGB, carried a higher fracture risk than that of the general population, with an odds ratio of 2.3 (1.8-2.8) [67]. This risk was higher for fractures not only at the traditional osteoporotic sites of the hip, wrist, spine and upper arm, but also at nonosteoporotic sites such as the foot, leg or hand [67].…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 94%
See 2 more Smart Citations
“…The risk of fracture after bariatric surgery remains a matter of controversy; a study showed twice the risk in patients who have had bariatric surgery compared to the rates of incidence based on the general population, 97 the other study showing no increase of the risk of fracture in the first two years after surgery compared to a non-operated obese population. 98 There are very many recent recommendations in clinical practice focusing on patients treated with bariatric surgery 84,99,100 (Table 1). While these recommendations are the subject of extreme care by their authors using all of the relevant and available data literature, certain recommended measures are not always based on medical data [101][102][103] A randomized study showed that taking 50,000 IU ergocalciferol weekly gave at one year higher values of 25-hydroxy vitamin D than in the daily intake of 800 IU.…”
mentioning
confidence: 99%